2021
DOI: 10.1021/acsami.1c18679
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of ZnO Nanobrushes by H2–C2H2 Plasma Etching for H2 Sensing Applications

Abstract: Zinc oxide has widespread use in diverse applications due to its distinct properties. Many of these applications benefit from controlling the morphology on the nanoscale, where for example gas sensing is strongly enhanced for high surface-to-volume ratios. In this work the formation of novel ZnO nanobrushes by plasma etching treatment as a new approach is presented. The morphology and structure of the ZnO nanobrushes are studied in detail by transmission and scanning electron microscopy. It is revealed that Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 70 publications
(142 reference statements)
0
11
0
Order By: Relevance
“…CasaXPS (version 2.3.16) was used for this purpose. SEM, XRD, and micro-Raman studies were conducted as previously reported. , The WITec micro-Raman spectrometer was used in this study, and a 532 nm laser served as the excitation source. A monochromator with a 1200 groove·mm –1 grating was used to disperse the scattered light and afterward focused onto a charge-coupled detector (CCD, Wright Instruments, Ltd.).…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…CasaXPS (version 2.3.16) was used for this purpose. SEM, XRD, and micro-Raman studies were conducted as previously reported. , The WITec micro-Raman spectrometer was used in this study, and a 532 nm laser served as the excitation source. A monochromator with a 1200 groove·mm –1 grating was used to disperse the scattered light and afterward focused onto a charge-coupled detector (CCD, Wright Instruments, Ltd.).…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…The electrical resistance changes as the sensing material of MOS is exposed to air and H 2 atmosphere, and the concentration of H 2 can be monitored in real time by analyzing the electrical signal [14]. Among them, ZnO is a typical wide-band gap semiconductor with the advantages of non-toxic and stable physical and chemical properties [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Volatile organic compounds (VOCs), which originate from multiple sources such as household items, cooking appliances, paint, oil refineries, and vehicle exhaust emissions, are highly hazardous vapors that significantly affect human health and air quality in various industrial environments. Despite having been investigated extensively over the past few years, the sensing properties toward VOCs need to be improved continuously to meet the most up-to-date requirements for specific applications and to withstand the harsh industrial environments, especially when using heterostructures or heterojunctions of two or more metal oxides. The selective detection of low concentrations of VOCs is highly important to underpin the continuous monitoring of human health and for environmental safety . Among the various types of materials available, the semiconducting–metal oxide-based chemo-resistive sensors are considered to be promising candidates for the detection of VOCs, , especially those comprising heterostructures/heterojunctions containing two or more different oxides, as these materials show excellent potential for their application in portable solid-state devices because of their low cost, high efficiency, simple preparation method, and good stability. In the context of real-world applications, the response parameter is influenced by several factors, including the morphology, microstructure, defects, and heterojunctions of the VOC sensors as well as the relative humidity . The response and selectivity performance of solid-state gas sensors can be improved further through control of their properties and, especially, by developing new multilayered or heterostructured oxides with a coating of Al 2 O 3 nanofilms.…”
Section: Introductionmentioning
confidence: 99%
“…5 Among the various types of materials available, the semiconducting−metal oxide-based chemo-resistive sensors are considered to be promising candidates for the detection of VOCs, 2,6 especially those comprising heterostructures/heterojunctions containing two or more different oxides, as these materials show excellent potential for their application in portable solid-state devices because of their low cost, high efficiency, simple preparation method, and good stability. 1−9 In the context of real-world applications, the response parameter is influenced by several factors, including the morphology, 10 microstructure, defects, and heterojunctions of the VOC sensors as well as the relative humidity. 6 The response and selectivity performance of solidstate gas sensors can be improved further through control of their properties and, especially, by developing new multilayered or heterostructured oxides with a coating of Al nanofilms.…”
Section: Introductionmentioning
confidence: 99%